Orestes, from a Moral Model to an Authentic Free Person. The Depiction of Orestes by Aeschylus and Sartre. - Zhu, Xiaoyi (Stellenbosch : Stellenbosch University, 2016)
Thesis (MA)--Stellenbosch University, 2016.